2021
DOI: 10.1111/nph.17300
|View full text |Cite
|
Sign up to set email alerts
|

OsTPP1 regulates seed germination through the crosstalk with abscisic acid in rice

Abstract: Seed germination is essential for direct seeding in rice. It has been demonstrated that trehalose-6-phosphate phosphatase 1 (OsTPP1) plays roles in improving yield and stress tolerance in rice.In this study, the roles of OsTPP1 on seed germination in rice were investigated. The tpp1 mutant germinated slower than the wild-type (WT), which can be restored by exogenous trehalose. tpp1 seeds showed higher ABA content compared with WT seeds. The tpp1 mutant was hypersensitive to ABA and ABA catabolism inhibitor (Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…After that, we collected the germinating seeds at 6 h and 24 h after imbibed in the pure water. RNA sequencing (RNA-seq) libraries generated from total RNA with three independent replicates at 6 h and 24 h time points were deployed for the following analysis [ 20 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, we collected the germinating seeds at 6 h and 24 h after imbibed in the pure water. RNA sequencing (RNA-seq) libraries generated from total RNA with three independent replicates at 6 h and 24 h time points were deployed for the following analysis [ 20 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Imbibed seeds at 6 h, 12 h and 24 h after imbibition were harvested for enzyme extraction as previously described [ 20 ]. The assay kit from Jiancheng, biotechcompany (Nanjing, China) was used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The TPP gene family has been characterized as catalytic enzymes that mainly function in trehalose biosynthesis [18,76,77]. Despite their catalytic function, a portion of TPP genes has been identified to be involved in growth and development, response in abiotic and biotic stress and senescence [27][28][29][31][32][33]35,42,78,79]. Although wheat is one of the most economically important cereal crops, systemic studies on TPP homologs in wheat have not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…al. [27] reported that seed germination was regulated by OsTPP1 via crosstalk with the ABA catabolism pathway. In addition, high expression was also observed for TaTPP1, TaTPP8 and TaTPP9 in all developmental stages except dough development and ripening, suggesting that these genes might have a significant association with wheat developmental processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation